The Image of Law Enforcement Agencies: Current Status and Practices to Improve It - K. V. Mordvinov; U. A. Udavikhina (Теоретическая и прикладная юриспруденция)
In the current context of heightened economic and socio-political conflicts around the world, there is a crisis of confidence in the state institutions that provide public security. The authors of the article consider the problem of forming the image of law enforcement agencies in the Russian Federation and abroad as a way to increase confidence in the state system. An analysis of the current state of the Russian law enforcement system’s image is presented as well as the analysis of some reasons for the negative attitude of the population towards employees of penitentiary institutions and the role of mass media in shaping the image of law enforcement agencies. The analysis of the current state of the law enforcement system’s image is supplemented by a review of the results of studies of the reputation of law enforcement bodies in the US and European countries. Successful domestic and foreign practices of reputation enhancement and improvement of interaction with the population are analyzed, such as: informing on the activity and employees of law enforcement agencies in social networks, interaction with the population through specialized electronic portals and social networks, popularization of thematic books, films and TV series etc. The authors of the article proposed a set of measures to form a positive image of the law enforcement system, increase public confidence in the law enforcement agencies of the Russian Federation in the framework of the Center for Public Security and Law Enforcement Research at the North-West Institute of Management of the RANEPA.